What are the pulmonary ventilation strategies in the acute respiratory distress syndrome caused by COVID-19? A review study (Research, Society and Development, 2021)
In late 2019, a group of pneumonia cases associated with a new enveloped RNA coronavirus, spreading rapidly across continents and being known as the global COVID-19 pandemic. A smaller part of the population will not require hospitalization, however, some patients may develop a severe form of the disease and present complications such as an acute respiratory distress syndrome (ARDS) that requires invasive mechanical ventilation (IMV). Patients with ARDS by COVID-19 may present some specific characteristics in comparison with the typical forms of the syndrome, developing distinct phenotypes that have still been studied. Research has focused on clarifying protective lung ventilation (PLV) for these patients. This narrative review aimed to investigate the current worldwide experience in relation to PLV as management of ARDS associated with COVID-19 and to highlight IMV practices during a pandemic. After a process of tracking studies in the PubMed and BVS databases, 20 studies were selected. In most studies, the ventilatory management of patients is similar to the “classic” ARDS and, therefore, an PLV stood out as an important ally in the regression of ARDS in COVID-19 patients. However, the patients' phenotypic heterogeneity must be taken into account, especially regarding pulmonary mechanics and recruitment capacity. This study enabled scientific deepening of the similarities and differences of ARDS due to COVID-19 and other causes, in addition to allowing the formation of guidelines regarding initial ventilatory adjustments in patients with ARDS / COVID-19.